KONTROL GEOLOGI TERHADAP PEMUNCULAN MANIFESTASI PANASBUMI DI KAWASAN GUNUNG LAWU - Hurien Helmi; Hengky Kurniawan; Widi Adam (KURVATEK, 2020)
Gunung Lawu exhibit a prominent geothermal manifestation indicate promising geothermal potentials. The occurence of geothermal manifestations around the volcano indicates the occurrence of geothermal system in the area. Further detail investigations are required to confirm the occurrence of a well established geothermal system. Information about the geological factors controlling the geothermal manifestation is crucial to understand the geothermal system in an area. We analyze the previously available geological maps, lineament density, and geochemical analysis of the hotsprings in the area of Mt. Lawu to understand the correlation between the geological condition, especially the structural geology and the geothermal manifestation. Our results indicates that the occurence of the geothermal manifestations in the area is not directly correlated with the mapped major normal faults, but instead with the minor fracture regions. The lineament fractal density analysis also indicate that the high fractal density value does not coincide with the faults. The faults are located in the regions of medium fractal density. It is likely that the high lineament fractal density is mostly controlled by surface processes insetad of representing tectonic significance. The occurrence of the geothermal manifestations are located in the medium lineament density value, which may represented areas with minor fractures. Geochemical analysis supports this interpretation, analysis of the geochemistry of the samples taken from Cumpleng and Ngunut hotsprings shown bicarbonate-type. We also observe the presence of limonite and travertin deposits. This type of geothermal fluids and mineral deposits are commonly associated with the presence of fractures and cracks below or near the surface.